Climate Change and the Structural Resilience of the Doha Metro - Nikolis, Georgios; Chronopoulos, Petros; Griguta, Marin (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
In recent years, the Doha Metro has been the spearhead of Qatar’s effort to expand and upgrade its transportation infrastructure. In its current phase it will comprise three lines of an approximate overall length of 76 km and 37 stations. It is self-explanatory that such a significant infrastructure project should be a resilient one. The requirement for a 120 years design life for its permanent civil works structures implies that they should be resilient not only against the current environmental conditions, but also against future conditions due to the ongoing climate change. Resilient means that they will be able to serve their purpose under foreseen climatic changes during their design life. It is expected that climate change will increase the occurrence and intensity of weather events, especially in the Middle East and North Africa region. As per the AR5 assessment report of the Intergovernmental Panel on Climate Change Climate change will have profound impacts on a broad spectrum of infrastructure systems... transport being one of them. Furthermore, since transportation is interconnected with the economic and social welfare of an area, it is evident that the metro is a critical infrastructure system of Doha. In this paper, the climate change related main hazards on the Doha Metro permanent assets are presented along with the mitigation measures that have been adopted through provisions in the structural design and the materials used. Furthermore, suggestions for future contingency measures are made.